Isolation and Identification of pathogenic bacteria from drinking water from different regions in Nasseriya city from October 2014 to September 2015 - Qasim Hassan Wida’a (University of Thi-Qar Journal of Science, 2019)
In this study  isolate 134  organism from tap water at the time  reaserach through the seasens  winter and Sumer , to determinate   pathogenic bacteria of drinking  water from different regions  in   Nasseriya city from October 2014  to September 2015 , many  people  do not have access to clean and safe drinking water and many die of waterborne bacterial  infections, Salmonella typhi ,Salmonella typhimurium Streptococcus   faecalis  ,Esherichia coli ,Aeromonas hydrophilli  , Campylobacter jejuni ,Enterococcus faecalis    ,Staphylococcus  aureus  ,Citrobacter freundii,Citrobacter   diversus ,  Vibrio cholerae  Pseudomonas aeruginosa , Helicobacter pylori , Mycobacterium avium complex, (MAC   is presented, focusing on the biology  and ecology of the causal agents and on the diseases‘ characteristics and their life cycles in the environment, the  different city  ,that  contain many microbial pathogenic in tap water,the main bacteria present in human  feces for example  Enterobacter   cloacae    ,Pseudomonas aerogenosa   , important  sources of  bacterial fecal pollution  of waters are also briefly indicatedin  pollution and break point in  pipe line ,the aim of this study was to isolate and identify  bacteria from drinking water distributions system in Nasseriya city.